Private Acts of Parliament - Richardson, Sir Ivor (Victoria University of Wellington Law Review, 2010)
The article explains the role that Private Acts of Parliament have played and still play. It does so by recounting their historical development and then discussing some 70 Bills and their progress through the Parliamentary processes. The narrative follows a broad subject-matter classification of Private Bills which are promoted by private individuals, local institutions, companies, particular charities, associations and other corporate bodies for their own benefit, whereas Public Bills and Local Bills are directed to the functioning of Central Government and Local Government respectively.